2008
DOI: 10.4103/0189-6725.44177
|View full text |Cite
|
Sign up to set email alerts
|

Acute gastrointestinal emergencies requiring surgery in children

Abstract: The correct diagnosis of acute abdomen in children requires attention to clinical details and a high degree of suspicion. Early surgical intervention in doubtful cases may be necessary to solve diagnostic problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Other studies also showed male predominance but reported more to occur in infants as well. [2,8,9] This difference is because of the exclusion of ARM, atresias and NEC in our study.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Other studies also showed male predominance but reported more to occur in infants as well. [2,8,9] This difference is because of the exclusion of ARM, atresias and NEC in our study.…”
Section: Discussionmentioning
confidence: 73%
“…[2,10] We have excluded appendicitis from our study. Intussusception remains a commonest cause of bowel obstruction in infants and young children and has been reported by many authors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations